Reproductive biology of Scinax fuscomarginatus (Anura, Hylidae) in south-eastern Brazil - Toledo, L. F.; Haddad, CFB (Taylor & Francis Ltd, 2005)
The present study describes the reproductive biology of Scinax fuscomarginatus in a remnant of Cerrado in south-eastern Brazil. Observations were made between September 2002 and March 2004 at Estacao Ecologica de Itirapina, State of São Paulo, south-eastern Brazil. Breeding activities occurred in lentic and temporary bodies of water during the rainy season. Scinax fuscomarginatus exhibited a prolonged breeding pattern and a lek mating system. Males were smaller than females and defended individual calling areas through acoustic and physical interactions. Resident males consistently won encounters, but did not differ in size or mass from intruder males. Satellite behaviour was observed, but no female or amplected pair interception was registered. Scinax fuscomarginatus exhibited low operational sex ratios and the general reproductive mode in which eggs are laid in the water and tadpoles are aquatic. Amplexus was axillary and the eggs were deposited at the bottom of temporary ponds. Details on oocytes, egg masses, and eggs are included.
Keywords: Anura; aggressive behaviour; Cerrado; chorus organization; hylid treefrog; reproduction; temporary pond